Controlling an equilibrist Lego robot - Silva, Vinicius Corrêa Alves (2015)
This paper describes the design and implementation of a self-balancing two-wheeled robot, the Equilibrist Robot. The system is similar to the classical unstable, non-linear mechanical control problem of an inverted pendulum on a cart. Using the Linear Quadratic Regulator method and PID for state feedback, this paper shows a control algorithm that solves this problem. This control is able to reject disturbances and stabilize the system using a gyroscope. The control algorithm is implemented using Matlab and C- programing. The Equilibrist manages to stabilize itself in an upright position, reject disturbances and change its position.